CORPORATE IMAGINATION Plus : Five Steps to Translating Innovative Strategies Into Action - Bandrowski, James F., author 640050 (New York : Free Press ; London : Collier Macmillan, 1990)
Bandrowski shows that the business objective of developing new ideas is not to find solutions for their own sake, but to seek new ways of viewing a business and therefore compete more effectively. He develops a plan that will help a senior manager create and implement a company-wide vision.